2018
DOI: 10.1016/j.surg.2018.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Eye of the beholder: Risk calculators and barriers to adoption in surgical trainees

Abstract: Risk assessment tools are underutilized by trainees. Of importance, preference sets of clinicians appear to be unpredictable and may benefit more from a customizable, bespoke approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 42 publications
0
32
0
Order By: Relevance
“…Online risk calculators like the National Surgical Quality Improvement Program Surgical Risk Calculator can reduce variability and increase the likelihood that patients will engage in prehabilitation, but they have time-consuming manual data acquisition and entry requirements, which hinders their clinical adoption. [13][14][15][16][17][18] Emerging technologies can circumvent this problem. The MySurgeryRisk platform autonomously draws data from multiple input sources and uses machine learning techniques to predict postoperative complications and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Online risk calculators like the National Surgical Quality Improvement Program Surgical Risk Calculator can reduce variability and increase the likelihood that patients will engage in prehabilitation, but they have time-consuming manual data acquisition and entry requirements, which hinders their clinical adoption. [13][14][15][16][17][18] Emerging technologies can circumvent this problem. The MySurgeryRisk platform autonomously draws data from multiple input sources and uses machine learning techniques to predict postoperative complications and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional clinical decision-support systems require timeconsuming manual data acquisition and entry, which impairs their adoption. 8,33 Even the most successful and widely used static variable cutoff values do not accurately represent individual patient pathophysiology, as reflected by their suboptimal accuracy. 34,43,56 Parametric regression equations also fail to represent the complex, nonlinear associations among input variables, further limiting the accuracy of traditional multivariable regression models.…”
Section: Artificial Intelligence Predictive Analytics and Augmented Decision-makingmentioning
confidence: 99%
“…Other studies have shown that risk assessment tools are underutilized by trainees, favoring traditional models of communication due to lack of an electronic health record and clinical work ow interruption [25]. This remains true for attending surgeons as well.…”
Section: Discussionmentioning
confidence: 99%